Digital Marketing: A Review of the Literature in the last ten years - Arum Wahyuni Purbohastuti (Management Science Research Journal, 2024)
A literature review is used to discuss this research which aims to identify and analyze articles about digital marketing from 2015-2024. Data was obtained from Scopus taken using the Publish or perish (POP) analysis tool and Vos Viewer. The results of this research are based on data obtained from 200 articles, of, which in 2020 there were 42 articles discussing digital marketing. Meanwhile, in 2023 there will be 5 articles and in 2024 there will be no articles discussing digital marketing. Meanwhile, the data was processed using Vos Viewer to produce 10 clusters with 44 items.